The changing epidemiology of invasive pneumococcal disease after PCV13 vaccination in a country with intermediate vaccination coverage. Issue 50 (29th November 2018) - ,; Esteva, Cristina; de Sevilla, Mariona Fernández; Henares, Desiree; Grau, Immaculada; Marco, Francesc; Llaberia, Jaume; González-Cuevas, Araceli; Díaz, Alvaro; Martin, Maria Teresa; Sierra, Montserrat; Curriu, Margarida; et al.
Abstract: Background: We studied the impact of 13-valent pneumococcal conjugate vaccine (PCV13) on the incidence of invasive pneumococcal disease (IPD) and serotype distribution in a region with intermediate levels of vaccination (around 64% in children aged <2 years). Methods: Surveillance data on IPD cases reported by microbiologists participating in the Microbiological Reporting System of Catalonia during 2006–2014 were analysed. We compared estimated incidence rate (IR) ratios for serotypes included in PCV7, PCV10non7, PCV13non10 and non-PCV13 between the PCV7 (2006–2009) and PCV13 periods (2010–2014). IR were corrected for missing serotypes according to year and age groups: <2 years, 2–4 years, 5–64 years and ≥65 years. Results: A total of 9338 IPD cases were reported. Overall IPD incidence declined by 26.2% (from 16.4 to 12.1) in the PCV13 period. The largest decrease was observed in children aged 2–4 years (44.5%, from 37.4 to 20.8). Pneumonia fell in all age groups with the largest reduction in children aged 2–4 years (49.3%) and <2 years (42%). PCV13 serotypes decreased significantly in all age groups, from 52% (31.6 to 15.1) in children aged 2–4 years to 35% (22.8 to 14.8) in adults aged ≥65 years. Non-PCV13 serotypes rose by 13% (14.8 to 16.8) in people aged ≥65 years. Conclusions: In a region with intermediate vaccination coverage, the introduction of PCV13 has reduced the overall incidence of IPD, mainly due to the decrease in PCV13 serotypes in all age groups, suggesting herd immunity. Non-PCV13 serotypes have increased in adults aged ≥65 years, suggesting serotype replacement. Higher PCV13 vaccination coverage in children will further reduce IPD incidence in all age groups.